AMP-Activated Protein Kinase Directly Phosphorylates and Destabilizes Hedgehog Pathway Transcription Factor GLI1 in Medulloblastoma - Li, Yen-Hsing; Luo, Jia; Mosley, Yung-Yi C.; Hedrick, Victoria E.; Paul, Lake N.; Chang, Julia; Zhang, GuangJun; Wang, Yu-Kuo; Banko, Max R.; Brunet, Anne; Kuang, Shihuan; Wu, Jen-Leih; et al. (Cell reports (Cambridge), 2015)
The Hedgehog (Hh) pathway regulates cell differentiation and proliferation during development by controlling the Gli transcription factors. Cell fate decisions and progression toward organ and tissue maturity must be coordinated, and how an energy sensor regulates the Hh pathway is not clear. AMP-activated protein kinase (AMPK) is an important sensor of energy stores and controls protein synthesis and other energy-intensive processes. AMPK is directly responsive to intracellular AMP levels, inhibiting a wide range of cell activities if ATP is low and AMP is high. Thus, AMPK can affect development by influencing protein synthesis and other processes needed for growth and differentiation. Activation of AMPK reduces GLI1 protein levels and stability, thus blocking Sonic-hedgehog-induced transcriptional activity. AMPK phosphorylates GLI1 at serines 102 and 408 and threonine 1074. Mutation of these three sites into alanine prevents phosphorylation by AMPK. This leads to increased GLI1 protein stability, transcriptional activity, and oncogenic potency. [Display omitted] •AMPK blocks Shh-induced transcriptional activity•AMPK reduces GLI1 protein level and stability•AMPK phosphorylates GLI1 at serines 102 and 408 and threonine 1074•GLI13A protein is resistant to AMPK and has higher stability and oncogenic ability Li. et al. show that AMPK is linked to the Hh signaling pathway. Activation of AMPK phosphorylates GLI1, a Hedgehog transcriptional activator, and inhibits Hh activity. GLI1 phosphorylation decreases GLI1 protein stability and reduces cell growth, colony formation, and tumor growth in mice.